Online Social Network Analysis using Machine Learning Techniques - Uttama Garg (International Journal of Advanced Science and Technology, 2020)
Now a days Social Media become the most powerful plateform to express your views and opinion. Orkut, Facebook, Twitter, Instagram are the mean of human life. Without social media or these social networking sites life will be stopped, I think. Most of the working and non working people are registered in one of these sites all of the world. These social networking sites are the base of Sentiment Analysis and study of Opinion Mining. The study of tehse opinions can lead to a decision or some marketing benefits. Because on can easily estimate the theory of a human’s brain by studying his updates on these social networking sites. Now Machine Learning Algorithm like Linear Regression, Logistic Regression, Support Vector Machine, Naïve Bayes[1] Algorithm can be used to extract the conclusion of people’s opinion. To predict the most popular brand among Android and IOS smartphone, we are analyzing tweets in this paper.